Matrix Generation by First-Order Taylor Expansion in a Localized Manner - Jun Hu; Wen Zhang; Tong-Tong Qiu; Xue Lan (International Journal of Antennas and Propagation)
The method of moments is widely used, but its matrix generation is time-consuming. In the present paper, a localized multifrequency matrix-filling method is proposed. The method is based on the retarded first-order Taylor expansion of Green’s functions on each field point, which can reduce the number of callback Green’s functions and hence can solve double-surface integrals quickly. It is also based on the extraction of the common factors of different frequencies, and hence can sweep the frequency points quickly. Numerical examples are provided to validate the efficiencies of the proposed method.